Pengembangan Alat Peraga 3D IPA Untuk Melatih Pemahaman Konsep Kelas VII Pada Materi Tata Surya - Jantriyani, Jantriyani; Sjaifuddin, Sjaifuddin; Vitasari, Mudmainah (UNIB Press, 2024)
This research aimed to analyze the level of validity of 3D teaching aids with solar system material, and to analyze students' responses to 3D teaching aids using solar system material to train concept understanding. The research carried out is a type of research and development using a 4D model. In this research, instruments were used in the form of interview instruments, validation questionnaire instruments and student response questionnaires. The research subjects consisted of three media experts, three material experts, and three practitioner experts (science teachers) as well as 30 class VII middle school students. The results of the validation of 3D teaching aids on the solar system material as a whole obtained a validity percentage from the three experts (media experts, material experts and practitioner experts/science teachers), namely 91.25% in the